Bagaimana Harga Komoditas Unggulan dan Volume Ekspor Sumatera Selatan sebelum dan saat Pandemi Covid - 19 - Emilda Emilda; Muhammad Bahrul Ulum; Roswaty Roswaty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research is not only aimed at analyzing whether there are significant differences in the price levels of world rubber and palm oil commodities, and the value of exports in South Sumatra. But also, to find out how the influence of world rubber and palm prices on export levels in South Sumatra. The data in this study are monthly data on world rubber prices, world palm prices, and South Sumatra's export values before the pandemic (January 2018 - February 2020) and data on world rubber prices, world palm prices, and South Sumatra's export values during the pandemic (March 2020 – April 2022). Data analysis techniques in this study used SPSS and Eviews. This study uses SPSS in conducting an independent sample t-test to find out differences in world rubber prices, world palm prices, and South Sumatra's export values before and during the pandemic. Meanwhile, to find out whether there is an effect of world rubber prices and world palm prices on export levels in South Sumatra, a multiple regression test was carried out using Eviews. The results of this study indicate that there are differences in world rubber prices, world palm prices, and South Sumatra's export levels before and during the Covid-19 outbreak. Based on the results of the regression test, world rubber prices have an effect on export levels in South Sumatra, while world palm prices have no significant effect on export levels in South Sumatra. However, world rubber prices and world palm prices simultaneously affect the level of exports in South Sumatra. The government is expected to be able to support the development of downstream rubber and palm oil processing industries in order to increase the added value of rubber and palm products, increase production of rubber and palm oil, and export activities.